Design E-Book as an Online Learning Instruction for Teacher - Siti Khoiriyah; Rahmatika Kayyis; Nurmitasari, Nurmitasari; Rahman Cahyadi (Universitas Pancasakti Tegal, 2024)
Technology adaptation is not an easy thing for teachers to do with various tasks and high performance demands. This research aims to develop an e-book for teachers that has the characteristics of being easy to operate and distribute to various media or platforms, contains many files with content, and is supported by video tutorials. The method used is the ADDIE R&D model, with stages namely analysis, design, development, implementation, and evaluation. The subjects in this study amounted to 30 teachers. The results of this study showed a good response to the e-book in the aspects of interest and benefits, with an average value of 4.18. This means that the e-book developed is considered feasible by teachers to be used as a guide in preparing digital learning media and managing online learning.